Ekranisasi Novel Balada Si Roy Karya Gol A Gong Ke Film Balada Si Roy Karya Sutradara Fajar Nugros - Irsan Amulya; Hasanuddin WS (Universitas Negeri Padang, 2024)
According to Eneste (1991:60) the use of the word ecranization is used as a sharper term than the term adaptation. Ecranization consists of 3 types, namely addition, reduction, and change of variation. Ecranization is usually used for films adapted from novels. The focus of the research on the novel Balada Si Roy by Gol A Gong to the film Balada Si Roy by Fajar Nugros is to identify forms of ecranization which include reduction, addition, and change of variation related to elements of characters, plot events, and elements of the setting. This research is a qualitative research using descriptive methods. According to Sugiyono (2017:8) stated that qualitative analysis focuses on the designation of meaning, description, explanation and placement of data in their respective contexts and expressing them in the form of words rather than numbers. Siswantoro (2016:55) Literary research is descriptive in nature, therefore his research is also classified as a descriptive research method. With this method, researchers can describe changes in elements of characters, plot, and setting in the ecranization of the novel Balada Si Roy by Gol A Gong to the film Balada Si Roy by director Fajar Nugros. Based on the data obtained in the research above, the following conclusions can be drawn. (1) The reduction aspect consists of 97 reductions in character elements, plot events, and settings, and time that are not shown in the Balada Si Roy film by director Fajar Nugros. (2) The addition aspect consists of 56 additions of character elements, plot events, and setting elements that are not in the Balada Si Roy novel by Gol A Gong, and (3) The change aspect consists of 46 changes in variations of character elements, plot events, and settings